HISTORY OF THE METEORITE COLLECTION OF THE RUSSIAN ACADEMY OF SCIENCES - Ivanova M.A.; Nazarov M.A. (My University, 2006)
The meteorite collection of the Russian Academy of Sciences is the largest and most unique collection of meteorites in Russia, and one of the famous meteorite collections in the world. The collection contains more than 1230 meteorites and approximately 25 000 individual samples. It also has samples of tektites and impactites, rocks from terrestrial impact craters. Practically all types of meteorites are represented in the collection, making it an excellent foundation for scientific investigations in Russia and worldwide. One hundred and ninety of the collection's meteorites came from territory that was under Russian jurisdiction at the time of accession. The meteorites are mostly represented by main masses and most of them are of historical significance. The Academy of Sciences' meteorite collection played a significant role in the formation of the science of meteoritics. As well as a scientific resource, the Academy of Sciences' meteorite collection is a unique social phenomenon. © The Geological Society of London 2006.